Kepuasan Akademik Mahasiswa Keperawatan Tahap Pendidikan Sarjana di Banda Aceh: Academic Satisfaction of Undergraduate Nursing Students in Banda Aceh - Zahara Syarifah Thaherah; Hajjul Kamil; Yullzar; Ardia Putra; Rachmah (MPI Press, 2024)
Introduction: Academic satisfaction is a key indicator of the quality of education in higher education, which not only reflects the quality of service but also affects students' emotional well-being and the image and reputation of the institution. To improve the quality of academic services, higher education institutions must design innovative strategies that can optimally meet student needs. Objectives: This study aims to analyze the academic satisfaction of undergraduate nursing students. Method: This type of quantitative research uses a cross-sectional study design. The sampling technique used a total sampling of 330 undergraduate nursing students in 2021, 2022, and 2023. Data collection used the Student Satisfaction Inventory (SSI) questionnaire developed by Noel Levitz. Data analysis used descriptive statistics to assess the quality of education, guided by the size of the performance gap, the difference between the level of importance (importance rating), and the level of satisfaction (satisfaction rating), and the Importance Satisfaction Matrix analysis. Result: The study showed that the dimension with the highest level of conformity was service excellence (99.34%), while the lowest was campus support services (76.72%). The Importance Satisfaction Matrix contains 10 items from six dimensions that need serious attention in quadrant I, namely ease of access to computers and Wi-Fi networks, laboratory equipment and learning support, completeness of books/journals/literature, student rights are respected in campus life, well-organized lecture and exam schedules, curriculum is designed according to current needs, ease of new student registration procedures, ease of obtaining scholarship information, administrative services that are not long-winded, campus policies consider the interests and impacts on students. Conclusion: Undergraduate nursing education institutions must conduct periodic evaluations through the Faculty Quality Assurance Unit (SJMF) and campus support service facilities to ensure that student rights are guaranteed and the academic experience meets student expectations.